Rabies vaccinations at the rural–urban divide: successes and barriers to dog rabies vaccination programs from a rural and urban campaign in Zambia - Chazya, Ricky; Mulenga, Chilufya Aneta Susan; Gibson, Andrew D.; Lohr, Frederic; Boutelle, Cassandra; Bonaparte, Sarah; Sinywibulula, Oline; Thomas, Gareth; Bwalya, Patricia; Dautu, George; Munsimbwe, Linous; Muuka, Geoffrey; et al. (Frontiers in Veterinary Science, 2025)
IntroductionDog vaccination against rabies is considered one of the most effective strategies at preventing human deaths from rabies and is a key strategy for eliminating dog-mediated human rabies deaths. Traditional vaccination approaches in Zambia rarely collect operational data to assess coverage and inform subsequent campaigns.MethodsFollowing mass vaccination campaigns in rural (Itezhi tezhi) and urban (Lusaka) communities, we evaluated vaccination coverage achieved during the campaigns and characterized and estimated the dog population in these communities.ResultsHerd immunity (i.e., 70% vaccination coverage) was not achieved in the Lusaka campaign, likely due to challenges in pre-campaign community sensitization and distance to vaccination sites in the central point campaign approach. Dog population density showed a strong exponential association with human density (R2 = 0.89). Extrapolating this relationship nationally, there are an estimated 3.2 million dogs in Zambia (human-to-dog ratio 5.8:1) with 86% residing in rural communities at a very low density of less than 6 dogs per square kilometer.DiscussionAs most dogs were found to reside at very low densities, unique challenges to large-scale dog vaccination approaches may impact Zambia, due to high logistical costs associated with these settings. Prioritizing vaccinations in higher-density free-roaming dog populations could maximize effectiveness in resource-limited settings. Private veterinary services were commonly utilized among surveyed dog owners in urbanized communities in Lusaka, suggesting that they are an important collaborator for achieving rabies herd immunity. With improved knowledge of dog population and ownership characteristics, Zambia is well-prepared to design more effective vaccination campaigns as the rabies elimination program expands.